A bioactive polysaccharide TLH-3 isolated from Tricholoma lobayense protects against oxidative stress-induced premature senescence in cells and mice. (March 2018) - Pan, Wen-Juan; Ding, Qiu-Ying; Wang, Ya; Wang, Dan-Dan; Lu, Yong-Ming; Yang, Wei-Wei; Cai, Zheng-Nan; Cheng, Xiao-Du; Zhang, Wen-Na; Chen, Yan
Highlights: TLH-3 significantly increases the activity of antioxidant enzymes to forbid ROS production. TLH-3 ameliorated t-BHP-induced senescence by blocking p53-mediated inappropriate apoptosis. TLH-3 attenuates OSIPS by suppressing AGEs accumulation and MAO activity in premature aging mice. Abstract: To inform rational therapeutics to alleviate many senescence-related diseases in terms of the pathogenic pathways, we investigated the protective mechanisms of TLH-3 against premature senescence in tert- butyl hydroperoxide ( t- BHP)-induced human embryonic lung fibroblast (HELF) cells model andd -galactose-induced premature aging mice model. We demonstrate that TLH-3 ameliorated t- BHP-induced premature senescence, which is characterized by decreased senescence-associated β-galactosidase (SA-β-Gal) positive cells containing decreased senescence effector p53 level, via up-regulating bcl-2 and down-regulated bax and caspase-3 protein expression to block t-BHP-induced inappropriate apoptosis. Furthermore, d -galactose-induced mice exhibit senescence hallmark features such as increased senescence-associated secretory phenotype characterized by increased interleukin-6 (IL-6) secretion. TLH-3 diminished age-dependent increase in circulating IL-6, lipofuscin pigment (LPF) and advanced glycation endproducts (AGEs) accumulation, the monoamine oxidase (MAO) activity and the intensity of nuclear p53 staining, which was up-regulated byd -galactose stimulation in premature aging mice. Meanwhile, TLH-3 attenuatedd -galactose-induced histopathological lesions in premature aging mice.